Liagore pulchella, a new species of xanthid crab (Crustacea: Decapoda: Brachyura) from Vanuatu - Ng, Peter K.l.; Naruse, Tohru (Zootaxa, 2007)
Liagore pulchella, the third known species of the genus, is described from Vanuatu. The new species is easily recognizable from the two congeners by the complete absence of red spots on the dorsal surfaces of the carapace and the pereiopods. In addition, L. pulchella can be distinguished from L. rubromaculata (De Haan, 1835), and L. erythematica Guinot, 1971, by characters of the carapace, antenna, pereiopods and male first gonopod.